Molecular identification and genetic variations of forensically significant blow flies (Diptera: Calliphoridae) from Eastern India using DNA barcoding - Oishik Kar; Arka Mukherjee; Koustav Mukherjee; Debdeep Pramanik; Atanu Naskar; Dhriti Banerjee (PLoS ONE, 2025)
Flies, especially those from the Calliphoridae family, play a crucial role in decomposition and are the first to colonize a cadaver. Firstly, accurate species identification is a prerequisite for entomological evidence-based calculation of postmortem interval (PMI). While morphological criteria for identifying the species of adult blow flies exist, there are either absent or inadequate keys for younger stages. In all phases of blow fly development, molecular identification offers a quick and accurate procedure. It is widely known that mitochondrial cytochrome oxidase subunit I has the capacity for molecular identification but is ineffective in certain species. This study was conducted to assess the effectiveness of the cytochrome oxidase 1 gene in the identification of seventeen different species of calliphorid flies involving four genera, Calliphora, Chrysomya, Lucilia, and Hemipyrellia. In West Bengal, 2,977 blow fly specimens were gathered from four distinct geo-climatic zones. COI barcodes were able to confirm morphological identification through low K2P intraspecific genetic divergences (0% to 1%) and moderate to high K2P interspecific genetic divergences (0.39% to 12.29%). The Neighbour-Joining (NJ) analysis demonstrated well-supported reciprocal monophyly among the species. The species grouping was in agreement with morphological and molecular identifications. The four delimitation methods, BIN, ASAP, PTP, and GMYC, used for species identification produced similar results and facilitated the proper identification of species. Therefore, it can be concluded that COI barcodes are a highly successful alternative for the molecular identification of blow flies, facilitating forensic cases and biodiversity research in India.